2019
DOI: 10.2147/oajsm.s182178
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and youth soccer: an investigation into the level of asthma awareness and training among youth soccer coaches

Abstract: PurposeAsthma is the most common chronic disease among children. Exercise-induced bronchoconstriction which is common in asthmatic patients also occurs in individuals with no prior asthma diagnosis. Despite this and the fact that soccer is a high ventilation sport, there are no validated asthma management protocols in place for soccer coaches. This study aims to address 1) soccer coaches’ current knowledge on asthma, 2) whether there is a need for asthma-related training, and 3) any barriers to administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Our study is the first study to investigate the attitudes of young people with T1D, parents and sports coaches towards T1D management in a community sport setting. The interviews with all three groups identified that sports coaches lack adequate knowledge about T1D and that there is a lack of educational resources currently available to meet this need, Despite the benefits that existing educational resources have shown in the delivery of exercise programs, similar findings have been reported in previous research which showed parents and young people strongly expressed a lack of available resources for both T1D and other health conditions within the community (12,15,21,24,25). Consequently, the concerns expressed by parents and young people with T1D about the lack of current T1D exercise educational resources along with the participants in our study cohort reinforce the importance of developing educational resources to fill the gap in knowledge in sports coaches.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our study is the first study to investigate the attitudes of young people with T1D, parents and sports coaches towards T1D management in a community sport setting. The interviews with all three groups identified that sports coaches lack adequate knowledge about T1D and that there is a lack of educational resources currently available to meet this need, Despite the benefits that existing educational resources have shown in the delivery of exercise programs, similar findings have been reported in previous research which showed parents and young people strongly expressed a lack of available resources for both T1D and other health conditions within the community (12,15,21,24,25). Consequently, the concerns expressed by parents and young people with T1D about the lack of current T1D exercise educational resources along with the participants in our study cohort reinforce the importance of developing educational resources to fill the gap in knowledge in sports coaches.…”
Section: Discussionsupporting
confidence: 71%
“…Hence, based on the interviews conducted with the sports coaches in our study, the outstanding format idea was a simple resource that is small enough to fit with their other coaching equipment. A similar type of resource format has been previously identified for exercise and asthma, where coaches favoured a pocket guide (21).…”
Section: Discussionmentioning
confidence: 80%